Hatchery seed production of giant freshwater prawn, Macrobrachium rosenbergii using inland ground saline water in India. (11th March 2013) - Raizada, Sudhir; Javed, Hasan; Ayyappan, Subbanna; Mukhergee, Subas C; Maheshwari, Umesh K; Fielder, D Stewart
Abstract The suitability of inland saline water (ISW) from the Lahli‐Baniyani Fish Farm, Rohtak was investigated for the larval rearing of giant freshwater prawn (GFP), Macrobrachium rosenbergii. Six experiments were conducted. In Experiment‐I, 54% of the larvae metamorphosed to postlarvae (PL) in constituted seawater (CSW) whereas total mortality occurred at larval stages (LS)‐II and LS‐III in ISW with salinity of 12 g L−1. Larvae survived to LS‐IV in Experiment‐II, when ISW was supplemented with K+ SW. In Experiment‐III, total hardness in ISW was reduced serially, but K+ SW was supplemented. The larvae did not survive beyond LS‐V. In Experiment‐IV, ISW was amended with different ratios of Mg2+/Ca2+ and K+ SW. The larvae successfully metamorphosed to postlarvae with highest survival of 51.6% in Mg2+/Ca2+ ratio of 2.5. In Experiment‐V, eight larval cycles were run with water quality used in Experiment V, where all the cycles produced PL's with a survival rate of 20–67%. In Experiment VI, the larvae were reared in Mg2+/Ca2+ ratio of 2.5 and different levels of K+ to optimize its requirement. The ISW amended with K+ 80% SW and Mg2+/Ca2+ ratio of 2.5 was found to be commercially suitable for the seed production of GFP.